The effects of a single night of sleep deprivation on fluency and prefrontal cortex function during divergent thinking - Vartanian, Oshin; Bouak, Fethi; Caldwell, J. L.; Cheung, Bob; Cupchik, Gerald; Jobidon, Marie-Eve; Lam, Quan; Nakashima, Ann; Paul, Michel; Peng, Henry; Silvia, Paul J.; Smith, Ingrid (Frontiers in Human Neuroscience, 2014)
The dorsal and ventral aspects of the prefrontal cortex (PFC) are the two regions most consistently recruited in divergent thinking tasks. Given that frontal tasks have been shown to be vulnerable to sleep loss, we explored the impact of a single night of sleep deprivation on fluency (i.e., number of generated responses) and PFC function during divergent thinking. Participants underwent functional magnetic resonance imaging (fMRI) scanning twice while engaged in the Alternate Uses Task (AUT)—once following a single night of sleep deprivation and once following a night of normal sleep. They also wore wrist activity monitors, which enabled us to quantify daily sleep and model cognitive effectiveness. The intervention was effective, producing greater levels of fatigue and sleepiness. Modelled cognitive effectiveness and fluency were impaired following sleep deprivation, and sleep deprivation was associated with greater activation in the left inferior frontal gyrus during AUT. The results suggest that an intervention known to temporarily compromise frontal function can impair fluency, and that this effect is instantiated in the form of an increased haemodynamic response in the left inferior frontal gyrus.